An Unusual Case of Systemic Lupus Erythematosus and Hemophagocytic Syndrome - Saika Sharmeen; Nazia Hussain (Case Reports in Rheumatology)
Hemophagocytic syndrome (HS) or hemophagocytic lymphohistiocytosis (HLH) is an immune mediated phenomenon that can occur in the setting of an autoimmune disease, chronic immunosuppression, malignancy, or infection. It has been more commonly described in the pediatric population and less commonly in adults. We describe a case of a 52-year-old male who presented with a rash. He simultaneously met the Systemic Lupus International Collaborating Clinics (SLICC) criteria for the diagnosis of systemic lupus erythematosus (SLE) and the diagnostic criteria of HS as described in the hemophagocytic lymphohistiocytosis (HLH) 2004 trial. The bone marrow on autopsy showed the presence of abundant hemosiderophages with focal hemophagocytosis. SLE-associated HS might be underdiagnosed due to the overlap in clinical findings. This case represents the importance of prompt diagnosis and treatment of such a potentially fatal clinical syndrome.